The role of internal audit as a tool for detecting fraud - Dorota Burzyńska; Małgorzata Jabłońska (Economic and Environmental Studies (E&ES), 2018)
Fraud is a serious problem in the world, which often implies huge financial losses. The risk of fraud which is committed in companies is often considered insignificant and no preventive measures are taken which would minimize the possibility of its occurrence. Often, companies also do not have any tools which would allow quick detection of fraud and its perpetrators. Recent years, however, have seen a growing interest among entrepreneurs in implementing an independent and objective internal audit, which is the basis for good management. The aim of this article is to present the nature and role of internal audit in detecting various types of fraud in enterprises and to indicate its growing role in the risk management process. The article discusses the basic issues related to fraud in enterprises. Particular attention is paid to highlighting the importance of the risk management process in the internal audit activity.
Keywords: M40; M42; 330; internal audit; fraud; finances